Заходи контролю й нагляду за діяльністю персоналу Державної кримінально- виконавчої служби України щодо дотримання законності - Колб, О.; Колб, С.; Kolb, A.; Kolb, S. (Східноєвроп. нац. ун-т ім. Лесі Українки, 2013)
У статті досліджено міжнародно-правові акти, чинне законодавство, теоретичні підходи до контролю й нагляду за діяльністю персоналу кримінально-виконавчих установ. Подано визначення контролю за діяльністю персоналу виправних колоній щодо дотримання законності та внутрішнього порядку в процесі забезпечення особистої безпеки засуджених. Виділено види контролю за діяльністю персоналу Державної кримінально- виконавчої служби України. An activity of the ascertained by law subjects in promoting the implementation of the proper rules of law and legal instructions aimed at the fulfillment of the targets closely connected with the constitutional human law of life safety while serving the criminal sentence ascertained by law is regarded as control over the penal colonies staff activity in the observation of legitimacy and internal procedures to ensure the prisoners personal precautions. Analysis of existing criminal and penal Ukrainian legislation as well as operational search Ukrainian legislation allows defining the following types of control in the area of the Ukrainian State Penal Enforcement Service: 1) the public prosecutor’s supervision over the execution of criminal penalties; 2) institutional control; 3) the control exercised during a visit of penal institutions by the President of Ukraine and other officials; 4) judicial control; 5) public control over observance of the prisoners rights in the execution of criminal penalties; 6) international control; 7) the control of the Commissioner of the Supreme Council of Ukraine for Human Rights; 8) operational and investigative monitoring.
Measures of Control and Supervision Over the Staff of the Ukrainian State Penal Enforcement Service on the Observance of Legitimacy
Keywords: Державна кримінально-виконавча служби України; кримінально-виконавче право; права ув’язнених; State Penal Enforcement Service of Ukraine; criminal and penal law; the rights of prisoners